2021
DOI: 10.1002/ehf2.13360
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of transthyretin amyloidosis in patients with heart failure and no left ventricular hypertrophy

Abstract: Aims As evidenced by scintigraphy imaging, the prevalence of transthyretin (TTR) cardiac amyloidosis in heart failure patients with preserved ejection fraction (HFpEF) and left ventricular hypertrophy (LVH) ranges between 13% and 19%. The natural evolution of cardiac amyloidosis begins with the deposition of amyloid material in the myocardium, with LVH ensuing at later stages. With current imaging modalities, it is possible to detect TTR cardiac amyloidosis before the hypertrophic stage. The aim of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 24 publications
3
24
0
Order By: Relevance
“…In previous studies, the prevalence of ATTR-CA was reported to be between 13% and 19% in patients with unexplained LVH with HFpEF [5,14,15]. Also, in a study conducted on patients with HFpEF without LVH, it was reported that ATTR-CA was detected in 5% of these patients [2]. In our study, 65.9% of patients had LVH, of which approximately one-third was unexplained LVH.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In previous studies, the prevalence of ATTR-CA was reported to be between 13% and 19% in patients with unexplained LVH with HFpEF [5,14,15]. Also, in a study conducted on patients with HFpEF without LVH, it was reported that ATTR-CA was detected in 5% of these patients [2]. In our study, 65.9% of patients had LVH, of which approximately one-third was unexplained LVH.…”
Section: Discussionsupporting
confidence: 57%
“…Poisson regression analysis was used to evaluate the distribution of RF incidences in the ATTR-CA positive/negative groups. We expressed descriptive data as number (%) for categorical variables and compared them via the χ 2…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Devesa et al prospectively examined patients with heart failure and preserved ejection fraction (HFpEF) and no IWT, what they defined as a wall thickness less than 12 mm [ 13 ]. With the use of 99-Tc-DPD scintigraphy in 58 patients they found three patients with ATTR.…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies have reported a potential under‐diagnosis of specific aetiologies underlying HFpEF, as notably exemplified by the increasing recognition of the importance of cardiac amyloidosis in HFpEF patients. 22 , 23 It is also possible that patients with a suspected specific cause underlying HF were more likely to be referred to a reference centre, which would have led to an overestimation of some causes (such as ischaemia, valvular, or hypertrophic cardiomyopathies) in our study. However, our standardized investigations of these patients should have limited the under‐detection of specific aetiologies in idiopathic HFpEF patients.…”
Section: Discussionmentioning
confidence: 95%